Migration, memory, and diversity : Germany from 1945 to the present - Wilhelm, Cornelia, 1964- (Studies in contemporary European history ;, 2017)
"Within Germany, policies and cultural attitudes toward migrants have been profoundly shaped by the difficult legacies of the Second World War and its aftermath. This wide-ranging volume explores the complex history of migration and diversity in Germany from 1945 to today, showing how conceptions of 'otherness' developed while memories of the Nazi era were still fresh, and identifying the continuities and transformations they exhibited through the Cold War and reunification. It provides invaluable context for understanding contemporary Germany's unique role within regional politics at a time when an unprecedented influx of immigrants and refugees present the European community with a significant challenge"--Publisher description.